2015
DOI: 10.1002/imhj.21539
|View full text |Cite
|
Sign up to set email alerts
|

Infant Avoidance During a Tactile Task Predicts Autism Spectrum Behaviors in Toddlerhood

Abstract: The experience of touch is critical for early communication and social interaction; infants who show aversion to touch may be at risk for atypical development and behavior problems. The current study aimed to clarify predictive associations between infant responses to tactile stimuli and toddler autism spectrum, internalizing, and externalizing behaviors. This study measured 9-month-old infants’ (N = 561; 58% male) avoidance and negative affect during a novel tactile task in which parents painted infants’ hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 63 publications
2
35
0
Order By: Relevance
“…About 90% of ASD individuals show deficits in processing sensory information and express abnormal responses to stimuli (Marco EJ et al 2012). Tactile sensation is the most common sensory modality affected in ASD and the response abnormality to light touch is highly correlated with ASD severity (Tomchek SD and W Dunn 2007;Wiggins LD et al 2009;Mammen MA et al 2015;Orefice LL et al 2019). A range of tactile abnormalities, including reduced tactile detection threshold and allodynia have been reported in children with ASD (Brambilla P et al 2003;Abu-Dahab SM et al 2013;Kern JK et al 2013;Mikkelsen M et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 90% of ASD individuals show deficits in processing sensory information and express abnormal responses to stimuli (Marco EJ et al 2012). Tactile sensation is the most common sensory modality affected in ASD and the response abnormality to light touch is highly correlated with ASD severity (Tomchek SD and W Dunn 2007;Wiggins LD et al 2009;Mammen MA et al 2015;Orefice LL et al 2019). A range of tactile abnormalities, including reduced tactile detection threshold and allodynia have been reported in children with ASD (Brambilla P et al 2003;Abu-Dahab SM et al 2013;Kern JK et al 2013;Mikkelsen M et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…1B and 1C). Interestingly, the somatosensory system is highly affected in ASD and alterations in somatosensation are correlated to the severity of ASD (Tomchek SD and W Dunn 2007;Wiggins LD et al 2009;Mammen MA et al 2015;Orefice LL et al 2019). Therefore, we mainly focused on the somatosensory cortex and the side of this lateralized decrease in PV + neurons.…”
Section: Asymmetric Reduction In Pv + Cells In the Somatosensory Cortmentioning
confidence: 99%
“…Atypical responses to sensory stimuli (e.g., hypo- or hyper-responsiveness) have been associated with later developmental disabilities, poor motor skills, and difficulties with self-regulation (e.g., Ben-Sasson et al, 2007; DeGangi et al, 1993; Eeles et al, 2013; Mammen et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Whereas most infants are able to use early sensory experiences to engage in and learn from their environments, infants with atypical sensory responses (e.g., hypo- or hyper-responsiveness) have difficulty tolerating or responding to sensory input, which may have implications for later development. For instance, atypical sensory responses assessed as early as 8 months have been associated with developmental disabilities, poor motor skills, and difficulties regulating attention, emotion, and behavior (Ben-Sasson et al, 2007; DeGangi, Porges, Sickel, & Greenspan, 1993; Eeles et al, 2013; Mammen et al, 2015). …”
mentioning
confidence: 99%
“…Sensory sensitivity overlaps with conceptual models of temperament (e.g., Dunn, , Rothbart, ), and prior studies have found consistent associations between sensory sensitivity and higher temperamental negative reactivity during infancy and early childhood (e.g., Goldsmith, Van Hulle, Arneson, Schreiber, & Gernsbacher, ; O'Boyle & Rothbart, ). However, these two behavior patterns show distinct relations with child outcomes (Hopkins, Lavigne, Gouze, LeBailly, & Bryant, ; Mammen et al, ) and have unique developmental trajectories, with sensory sensitivity showing no significant change and temperamental negative reactivity showing increases during the first 2 years of life (Ben‐Sasson, Carter, & Briggs‐Gowan, ; Brooker et al, ; Wood, ). This suggests that sensory sensitivity and temperamental negative reactivity are related, but orthogonal, constructs.…”
Section: Introductionmentioning
confidence: 99%